2011
DOI: 10.1148/radiol.11101459
|View full text |Cite
|
Sign up to set email alerts
|

CT of the Pancreas: Comparison of Anatomic Structure Depiction, Image Quality, and Radiation Exposure between 320-Detector Volumetric Images and 64-Detector Helical Images

Abstract: Purpose:To prospectively compare 320-detector volumetric and 64-detector helical computed tomographic (CT) images of the pancreas for depiction of anatomic structures, image noise, and radiation exposure. Materials and Methods:This study was approved by the institutional review board, and written informed consent was obtained. A total of 154 patients (85 men, 69 women; age range, 26-85 years; mean age, 67 years) who underwent biphasic (arterial and pancreatic phase) contrast material-enhanced CT performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…Two different approaches were applied to evaluate pancreatic fat deposit complementarily, and the techniques described in the present study now facilitate similar studies. This study also supports and extends previous work on quantitative and qualitative assessment of the pancreas using MDCT with high spatial accuracy and fine resolution …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two different approaches were applied to evaluate pancreatic fat deposit complementarily, and the techniques described in the present study now facilitate similar studies. This study also supports and extends previous work on quantitative and qualitative assessment of the pancreas using MDCT with high spatial accuracy and fine resolution …”
Section: Discussionsupporting
confidence: 90%
“…This study also supports and extends previous work on quantitative and qualitative assessment of the pancreas using MDCT with high spatial accuracy and fine resolution. 49 In conclusion, the present study showed that, compared with white participants, Korean participants had a significantly lower pancreatic volume and tended to have greater fat content in the pancreas, and these factors were associated with the disposition index, a dynamic marker reflecting insulin secretory function for insulin resistance. These disadvantageous constitutional features in the pancreas might make Koreans, and possibly other Asians, more vulnerable to pancreatic β-cell damage even though they might have slightly less insulin resistance than white people, who might be protected against the same degree of insulin resistance with a relatively larger β-cell reservoir.…”
Section: Discussionmentioning
confidence: 53%
“…For the subcutaneous fat of the anterior abdominal wall, the constant position was set at the level of the aortic bifurcation [30,31]. Aortic attenuation was measured at the level of the origin of the right renal artery.…”
Section: Image Quality Analysismentioning
confidence: 99%
“…Jika hasil evaluasi kedua responden dihitung maka kesimpulan yang diperoleh ada perbedaan yang signifikan antara hasil citra pankreas fase vena porta pada CT Scan abdomen kontras tanpa dan dengan reformat MinIP. Butir pertanyaan yang digunakan selain telah diuji dengan menggunakan uji korelasi Spearman Rank yang menunjukan ada hubungan antara pertanyaan satu dan lainnya, butir pertanyaan juga mengacu pada jurnal yang ditulis oleh (Goshima, 2011) yang mengatakan bahwa dengan modalitas CT Scan 64 slice dapat membedakan struktur anatomi pankreas dan organ-organ disekitar arteri splenica, arteri celiaca, duodenum, vena mesenterika superior dan arteri pancreaticodudenal dengan baik. Namun penelitian yang dilakukan ini tanpa menggunakan reformat MinIP.…”
Section: Pembahasanunclassified